Implementasi Karakter Profil Pelajar Pancasila pada Pembelajaran IPAS Kelas IV SDN 19 Cakranegara - Isyatul Rodia; Moh. Irawan Zain; Ilham Handika (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to describe the implementation of the Independent and Mutual Cooperation dimensions of the Pancasila Student Profile in fourth-grade Natural and Social Sciences (IPAS) learning at SDN 19 Cakranegara. The study employed a qualitative descriptive approach. Data were collected through classroom observations, interviews with the principal and fourth-grade teacher, and document analysis of teaching modules, lesson plans, and assessment instruments. Data were analyzed using the interactive model of data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the Pancasila Student Profile was systematically integrated into the planning, implementation, and evaluation stages of learning. During the planning stage, both dimensions were incorporated into learning objectives, the Problem Based Learning model, learning activities, worksheets, instructional media, and assessment. During classroom implementation, students demonstrated independent learning through individual responsibility and active participation, while mutual cooperation was reflected in collaborative discussions, group problem-solving, and presentations. The evaluation process also assessed knowledge, skills, and character development. The results showed that the Independent and Mutual Cooperation dimensions each appeared with the same frequency (50%), indicating a balanced implementation in IPAS learning. These findings suggest that integrating the Pancasila Student Profile into classroom learning effectively supports character development while achieving the objectives of the Merdeka Curriculum.